Prevalence of Gestational Diabetes Mellitus among Pregnant Women Undergoing Oral Glucose Tolerance Test (OGTT) at Chitwan Medical College and Teaching Hospital - Kafle, Deepak; Gupta, Bijaya Kumar; Timalsina, Santosh; Mandal, Fuleshwar (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Gestational Diabetes Mellitus (GDM) is defined as glucose intolerance of variable severity in which spontaneous hyperglycemia develops during pregnancy. GDM is affecting approximately 14% of pregnancies worldwide, representing approximately 18 million births annually. GDM increases the risk of adverse maternal and perinatal outcome and also increases risk of future diabetes to the mother and their child. MATERIALS AND METHODS: The cross-sectional study was carried out over 8 months in 149 pregnant subjects of gestation period between 24 and 28 at Chitwan Medical College Teaching Hospital (CMCTH). All pregnant women were considered for 50gm Glucose Tolerance Test (GCT). Those pregnant subjects with GCT ≥ 140mg% only undergo 100 gm Oral Glucose Tolerance Test (OGTT) & plasma glucose were estimated at the interval of 0,1,2 and 3 hours respectively. The GDM was diagnosed after performing OGTT based on Carpenter-Coustan Criteria. RESULTS: In our study from 149 study population, the frequency of normal & abnormal GCT in pregnant women was 111(74.50%) & 38(25.50%) respectively. Out of 149 subjects only 38 pregnant women have abnormal GCT in which only 23 have done OGTT test. Among 23 subjects the presence of GDM was found in 9 subjects with 39.10% whereas GDM was not found in 14 subjects with 60.9%. The prevalence of GDM among 149 populations was found to be 9 which is 6.04%. CONCLUSIONS: The prevalence of GDM among 149 populations was found to be 6.04%. The real burden, risk factors, and potential preventative interventions of gestational diabetes mellitus must also be measured in large observational studies for finding the correlation to assess the severity of the disease.